Does the availability of snack foods in supermarkets vary internationally? - Thornton, L; Cameron, A; McNaughton, SA; Waterlander, W; Sodergren, M; Svastisalee, C; Blanchard, L; Liese, A; Battersby, S; Carter, M; Sheeshka, J; Kirkpatrick, S; et al. (2013)
BACKGROUND: Cross-country differences in dietary behaviours and obesity rates have been previously reported. Consumption of energy-dense snack foods and soft drinks are implicated as contributing to weight gain, however little is known about how the availability of these items within supermarkets varies internationally. This study assessed variations in the display of snack foods and soft drinks within a sample of supermarkets across eight countries. METHODS: Within-store audits were used to evaluate and compare the availability of potato chips (crisps), chocolate, confectionery and soft drinks. Displays measured included shelf length and the proportion of checkouts and end-of-aisle displays containing these products. Audits were conducted in a convenience sample of 170 supermarkets across eight developed nations (Australia, Canada, Denmark, Netherlands, New Zealand, Sweden, United Kingdom (UK), and United States of America (US)). RESULTS: The mean total aisle length of snack foods (adjusted for store size) was greatest in supermarkets from the UK (56.4 m) and lowest in New Zealand (21.7 m). When assessed by individual item, the greatest aisle length devoted to chips, chocolate and confectionery was found in UK supermarkets while the greatest aisle length dedicated to soft drinks was in Australian supermarkets. Only stores from the Netherlands (41%) had less than 70% of checkouts featuring displays of snack foods or soft drinks. CONCLUSION: Whilst between-country variations were observed, overall results indicate high levels of snack food and soft drinks displays within supermarkets across the eight countries. Exposure to snack foods is largely unavoidable within supermarkets, increasing the likelihood of purchases and particularly those made impulsively.